Influence of Multiple Thermomechanical Processing of 3D Filaments Based on Polylactic Acid and Polyhydroxybutyrate on Their Rheological and Utility Properties - Plavec, Roderik; Horváth, Vojtech; Hlaváčiková, Slávka; Omaníková, Leona; Repiská, Martina; Medlenová, Elena; Feranc, Jozef; Kruželák, Ján; Přikryl, Radek; Figalla, Silvestr; Kontárová, Soňa; Baco, Andrej; et al. (Polymers, 2022)
This study focused on material recycling of a biodegradable blend based on PLA and PHB for multiple applications of biodegradable polymeric material under real conditions. In this study, we investigated the effect of multiple processing of a biodegradable polymer blend under the trade name NONOILEN®, which was processed under laboratory as well as industrial conditions. In this article, we report on testing the effect of blending and multiple processing on thermomechanical stability, molecular characteristics, as well as thermophysical and mechanical properties of experimental- and industrial-type tested material suitable for FDM 3D technology. The results showed that the studied material degraded during blending and subsequently during multiple processing. Even after partial degradation, which was demonstrated by a decrease in average molecular weight and a decrease in complex viscosity in the process of multiple reprocessing, there was no significant change in the material's thermophysical properties, either in laboratory or industrial conditions. There was also no negative impact on the strength characteristics of multiple processed samples. The results of this work show that a biodegradable polymer blend based on PLA and PHB is a suitable candidate for material recycling even in industrial processing conditions. In addition, the results suggest that the biodegradable polymeric material NONOILEN® 3D 3056-2 is suitable for multiple uses in FDM technology.
Keywords: polylactic acid; polyhydroxybutyrate; 3D printing; material recycling